Insights into the synergy effect in dual single-atom catalysts on defective CeO2 under CO2 hydrogenation - Park, Dahee; Hong, Seunghwa; Han, Jaebeom; Kim, Yongjoo; Park, Minhee; Lee, Byunghyun; Song, Yejin; Koo, Hye Young; Yang, Sangsun; Lee, Won Bo; Park, Jeong Young (Elsevier BV, 2025)
Single-atom catalysts are extensively researched for their superior catalytic performance owing to their atomiclevel active sites. Challenges associated with controlling single atoms have led to numerous attempts to develop efficient synthesis methods. Herein, we highlight a straightforward single-atom catalyst synthesis approach based on aerosol-assisted spray pyrolysis. We dispersed single-atom metals (Pt, Co, and Ni) on mesoporous defective CeO2 and employed the prepared catalysts for CO2 hydrogenation. We also prepared dual single-atom catalysts (Pt/Co and Pt/Ni), which exhibit dual-metal synergy owing to electronic metal-metal interactions. In these systems, CeO2 acts as the support, while the dual single-atom metals serve as active sites. We investigated the atomic-defect properties of catalytic sites and evaluated the catalytic performance for CO2 conversion, CO selectivity, and long-term stability based on the metal species. We particularly focused on surface deformation and synergistic effects arising from the incorporation of dual single-atoms. Our findings revealed that the atomicdefect properties of CeO2 and the pathways for CO2 and H2 activation are governed by the electronic metal-support interaction of the single-atom metal to CeO2 in the single-atom catalysts, and to the synergy between Pt and the transition metal as an electronic metal-metal interactions in the dual single-atom catalysts. Importantly, these critical outcomes were achieved via a one-step synthesis approach, highlighting the advancement of atomic-controlled catalysts, including single-atom and dual single-atom catalysts.